Āmhī pāhilele Phule - Rāyakara, Sītārāma (Ma Jotīrāva Phule Samatā Pratishṭhāna, 1981)
Reminiscences on Joti Govindrao Fule, 1827-1890, social reformer from Maharashtra by his associates and contemporaries.